TAFSIR AYAT ALAHKAM ABIL FADHOL ALSENORY: SEBUAH MODEL TAFSIR ANALISIS KRITIS - Muhammad Asif; Abdul Wadud Kasyful Humam (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2019)
This study tries to trace and find out the interpretation model of the tafsir Alahkam written by Abil Fadhol Alsenory, as an earlier tafsir of the pesantren in Indonesia. Based on the historical approach, philology, and analysis of critical discourse, by describing the socio-political context, as well as the author's response to the socio-religious conditions at the time, the results indicate that there are one primer script and two manuscript copies of his students. The primer script was written directly by Abil Fadhol, while the manuscript was a copy of the students' writing from Abil Fadhol's explanation during his teaching moment. All of the three texts show that there are two social conditions as its background, namely 'restriction' policy of the New Order regime with NU, and the debate over religious polemic between traditionalists (NU) and modernists in Indonesia in the second half of the 20th century. From this, it was revealed that Abil Fadhol's interpretation model was very critical but contextual and applicable to its surrounding social conditions.